Pemberdayaan Siswa Melalui Program Bisnis Digital Berbasis Islamic Entrepreneurship di Sekolah MAN 1 Deli Serdang - Bebi Asdilvira; Yogi Putra (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
This community service program aims to empower students. The lack of digital business literacy and knowledge about Islamic entrepreneurship in Islamic-based schools, as well as the application of sharia business principles, are the main drivers of this program. The activity implementation technique uses the Participatory Action Research (PAR) methodology. Problem identification, needs analysis, preparation of materials and instruments, pre-testing, training in Islamic business ethics and entrepreneurship theory, digital business practices, mentoring, post-testing, and program evaluation are some of the steps included in the activity. A total of 60 12th-grade students and ten instructors participated in this activity. The results showed that students' knowledge of sharia-based digital business, digital marketing skills, and entrepreneurial drive all increased. Student interest in starting a business increased by 78%, and participants' understanding of digital literacy increased by 85%. Furthermore, the program successfully instilled the ideals of Islamic entrepreneurship, such as accountability, honesty, and trustworthiness, as well as the prohibition of usury in digital business operations. In addition to encouraging the development of an Islamic digital business community within the educational environment, this community service program helps students develop personalities with noble morals, creativity, and adaptability.